2018
DOI: 10.3389/fmicb.2018.00258
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Escherichia albertii: Co-occurrence of β-Lactamase and MCR-1 Encoding Genes

Abstract: Escherichia albertii is an emerging member of the Enterobacteriaceae causing human and animal enteric infections. Antimicrobial resistance among enteropathogens has been reported to be increasing in the past years. The purpose of this study was to investigate antibiotic resistance and resistance genes in E. albertii isolated from Zigong city, Sichuan province, China. The susceptibility to 21 antimicrobial agents was determined by Kirby–Bauer disk diffusion method. The highest prevalence was tetracycline resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
2
23
1
Order By: Relevance
“…We found that MPE isolates carried other antimicrobial resistance genes, especially ESBLs, ampC, and carbapenemase genes; particularly in the IncHI2A-type mcr-1 -harboring plasmids, multiple resistance genes were identified. This was in agreement with previous studies ( Mediavilla et al, 2016 ; Bi et al, 2017 ; Rhouma and Letellier, 2017 ; Li Q. et al, 2018 ; Zheng et al, 2019 ). A study in China investigated the coexistence of ESBLs and mcr-1 genes in E. coli isolated from chickens between 2008 and 2014 and concluded that mcr-1 -positive strains carry at least one ESBL ( Wu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 94%
“…We found that MPE isolates carried other antimicrobial resistance genes, especially ESBLs, ampC, and carbapenemase genes; particularly in the IncHI2A-type mcr-1 -harboring plasmids, multiple resistance genes were identified. This was in agreement with previous studies ( Mediavilla et al, 2016 ; Bi et al, 2017 ; Rhouma and Letellier, 2017 ; Li Q. et al, 2018 ; Zheng et al, 2019 ). A study in China investigated the coexistence of ESBLs and mcr-1 genes in E. coli isolated from chickens between 2008 and 2014 and concluded that mcr-1 -positive strains carry at least one ESBL ( Wu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 94%
“…In countries such as Japan and Norway, the number of infections caused by E. albertii is increasing, which is a warning sign that the bacterium is causing problems around the world (24). E. albertii is important not only for its pathogenicity and its role in gastroenteritis in the world but also for its resistance to certain antibiotics (6,7). Therefore, it is important to continuously examine patients with diarrhea and urinary tract infections to detect E. albertii.…”
Section: Discussionmentioning
confidence: 99%
“…Its misdiagnosis as Enteropathogenic Escherichia Coli (EPEC), Enterohemorrhagic Escherichia coli (EHEC), or other pathogenic bacteria has continued from the past to the present. Recently, its pathogenic potential has been strengthened by identifying strains with multiple antibiotic resistance (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the recently discovered plasmid‐born mcr‐1 already is found on extended‐spectrum β‐lactamase multidrug resistance plasmids (e.g. Li et al , ), while plasmid‐mediated multidrug efflux cassettes are also linked to multidrug‐resistant infections in the hospital setting (Kim et al , ). While it is shown that originally these resistance elements have been selected due to a direct effect of polymyxin and olaquindox to promote animal growth their enrichment in the animal gut in response to florfenicol, a non‐cognate class of antibiotic was alarming.…”
Section: Discussionmentioning
confidence: 99%